Batteries in Service of Human Health. (1st September 2022) - Takeuchi, Esther S.; Brock, David; Housel, Lisa M.; Marschilok, Amy; Takeuchi, Kenneth
Abstract : Advances in treatment and diagnosis of human health demand advances in energy storage providing small, adaptable, predictable, and reliable systems. This article summarizes key milestones in the adoption of batteries used for implantable medical applications, provides details about several of the dominant battery chemistries currently powering medical devices, and provides comment on the future impact of advances in the battery field on medical devices.